Effects Of Relationship Marketing Upon Nz Micro-Enterprise Internationals Within The Asian Marketplace - Pickering , Paul; J Kingshott, Russel P (KINERJA, 2010)
The main purpose of this research was to establish whether the exporting NZ micro-enterprise (MCE) is able to leverage relational marketing practices with international distributors in the Asian region. This is an important consideration when entering new markets given the resource constraints of these firms. A qualitative approach using semi-structured interviews was used to ascertain the precise nature of their international distributor relationships. Our research findings suggest that those firms capable of building trust-based relationships are able to successfully enter key Asian markets. Furthermore, they were found to achieve a range of international performance outcomes usually associated with much larger firms. The research and managerial implications of such counter-intuitive findings are discussed.